2021
DOI: 10.1016/j.compositesa.2020.106156
|View full text |Cite
|
Sign up to set email alerts
|

Interface tailoring between flax yarns and epoxy matrix by ZnO nanorods

Abstract: The ideal mechanical performance of a composite is controlled by the level of interfacial adhesion and to overcome the incompatibility issues between plant fibres and polymeric matrices, the surface of flax yarns has been modified by zinc oxide (ZnO) nanostructures. The ZnO nanorods were synthesized through a lowtemperature hydrothermal treatment, and several parameters have been analysed in order to obtain a uniform and homogeneous ZnO interphase, such as the number of the seeding cycles, the growth reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 83 publications
(94 reference statements)
1
17
1
Order By: Relevance
“…This confirmed that the removal of MB in the presence of hexagonal ZnO nanorods can be attributed to the ability of such structures to promote the production of radical species such as superoxide anions ( • O 2 − ) and hydroxyl radicals ( • OH) [ 65 ] thanks to the electron-hole pairs mechanism [ 24 ]. No substantial difference between the specimens was observed: in both cases a kinetic of first order (Equation (8)) well describes the MB removal time ( t ) in accordance with other authors [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ...…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This confirmed that the removal of MB in the presence of hexagonal ZnO nanorods can be attributed to the ability of such structures to promote the production of radical species such as superoxide anions ( • O 2 − ) and hydroxyl radicals ( • OH) [ 65 ] thanks to the electron-hole pairs mechanism [ 24 ]. No substantial difference between the specimens was observed: in both cases a kinetic of first order (Equation (8)) well describes the MB removal time ( t ) in accordance with other authors [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ...…”
Section: Resultssupporting
confidence: 90%
“…In conclusion, the success obtained in the decoration of commercial veils allows introducing possible future application regarding their use as toughening material in composites. Their use in a neat form proved to reduce the extension of delaminated area after low velocity impact test [32] while the presence of ZnO nanorods on fiber surface enhances the adhesion between fibers and polymer matrix [56,57]. The high aspect ratio of ZnO nanorods after 3 h in 250 mL makes the electrospun veils suitable as a composite toughening element.…”
Section: Methodsmentioning
confidence: 99%
“…The difference between flax and glass fiber for epoxy resin indicates that flax is well suitable. One method to improve the bonding performance between flax fiber and epoxy resin is given by Sbardella et al (2021), suggesting the use of zinc oxide (ZnO) nanorods [30]. The decrease in PUR indicates adhesive application problems during the manufacturing process.…”
Section: Tensile Shear Strengthmentioning
confidence: 99%
“…Sbardella et al (2021) studied the growth of ZnO nanorods on flax yarn surface in order to improve the interfacial adhesion in flax/epoxy matrix biocomposites [ 69 ]. The hydrothermal treatment was provided to obtain highly oriented ZnO nanostructures, that is, hexagonal wurtzite nanorods.…”
Section: Hierarchical Interphase In Fully Synthetic and Hybrid Fibmentioning
confidence: 99%
“… ( a , b ) FE-SEM micrographs showing fracture surfaces for ZnO-flax/epoxy single yarn composites. Micro-computed tomography observation for the ZnO-modified flax yarn/epoxy matrix with ( c ) high-resolution micro-CT image of the flax embedded in the epoxy resin and ( d ) volumetric reconstruction of the flax yarn and the fracture zone: the flax yarn is represented in dark grey, the fracture zone in blue and the ZnO coating in red (reprinted with permission from Sbardella et al, 2021 [ 69 ]). …”
Section: Figurementioning
confidence: 99%